Dynamic association between AT(N) profile and cognition mediated by cortical thickness in Alzheimer’s continuum - Jang, Jae-Won; Kim, Yeshin; Kim, Seongheon; Park, Sang Won; Kwon, Sung Ok; Park, Young Ho; Lim, Jae-Sung; Youn, Young Chul; Hun Kim, Sung; Kim, SangYun (NeuroImage clinical, 2020)
•PPLGCM was used to test the biomarker sequence hypothesis based on AT(N) profiles.•Alzheimer’s pathologic change (e.g. A + T − (N)−) was insufficient to induce effects on cognitive dysfunction.•There was a significant direct path from altered cortical thickness to cognitive decline in A + T + (N)− profile.•Only the A + T + (N)+ profile showed significant mediation effect of cortical thickness.•Sequential effects between brain MRI and cognition changes varied by AT(N) profile.•Dynamic changes in biomarker relations in the cascade model should be considered. The recently-proposed National Institute on Aging and Alzheimer’s Association research framework organizes Alzheimer’s disease (AD) biomarkers based on amyloid/tau/neurodegeneration (AT(N)). This study investigated the mediating effect of structural change in brain MRI on changes in cognitive function according to initial AT(N) profiles. We included 576 subjects (cognitively unimpaired (N = 136), mild cognitive impairment (N = 294), dementia (N = 146)) from the Alzheimer’s disease Neuroimaging Initiative study. The parallel-process latent growth curve model was applied to test the mediational effect of cortical thickness growth trajectory between the initial AT(N) profiles and cognitive growth trajectory. In Alzheimer’s continuum, only the A + T + (N)+ profile showed a mediational effect of the cortical thickness growth trajectory. A + T − (N)− was not sufficient to induce direct or indirect effects on cognitive dysfunction, and A + T + (N)− showed a significant direct path from an altered cortical thickness to cognitive decline. The sequential effect between changes in brain MRI and cognition varied by baseline AT(N) profile, suggesting the dynamic changes in the relationships among biomarkers in the current cascade model.